Ecologia da dispersão de sementes do Pinheiro-do-Paraná (Araucaria Angustifolia) - Squinzani, Larissa Inês (2021)
The Paraná pine (Araucaria angustifolia) is a relictual conifer, threatened with extinction and is considered a key species in providing food for the fauna. Paraná pine seed is the only means of propagation for the species, and as it is a large and heavy seed, it depends on the dispersal being carried out by animals, which also consume a large part of the seeds produced annually. The animal-seed interactions can lead to different results, beneficial and harmful, for the plant, accordingly to the animal species involved, time of year, seed density and environment. Considering its importance for the fauna and the knowledge gap, the objective of this work was to verify specific characteristics in the opening of the seeds, for different animal species that use the seed as a food source, to present a detailed description and the elaboration of an identification key of the Paraná pine seed predation patterns. There were 35 patterns described for birds and mammals, demonstrating the potential for use in identifying consumer species as well as for use in animal-plant interaction studies. The effect of dispersal mode (according to disperser animal), distance from adult conspecifics, and disposition site on long-term recruitment success was also evaluated. The experimental design had two environments (forest and open field), on which each environment received 30 micro-habitat sampling stations (simulating deposition sites: 10 under conspecific; 10 far from conspecifics, next to landmark; and 10 far from conspecifics, without landmark), having each microhabitat three levels of dispersal type (intact buried seed; intact seed over the ground; partially preyed seed over the ground), totaling 900 seeds. The type of dispersion given by the disperser was significant for survival, and the buried seeds were the only ones to have survived until the last reading.